2007
DOI: 10.1152/ajpheart.01395.2006
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) stimulates the phosphorylation of JAK2, IRS-1 and Akt in rat heart in vivo: role of the AT1 and Mas receptors

Abstract: Angiotensin (ANG) II exerts a negative modulation on insulin signal transduction that might be involved in the pathogenesis of hypertension and insulin resistance. ANG-(1-7), an endogenous heptapeptide hormone formed by cleavage of ANG I and ANG II, counteracts many actions of ANG II. In the current study, we have explored the role of ANG-(1-7) in the signaling crosstalk that exists between ANG II and insulin. We demonstrated that ANG-(1-7) stimulates the phosphorylation of Janus kinase 2 (JAK2) and insulin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
117
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 54 publications
13
117
2
1
Order By: Relevance
“…It has been reported that Ang-(1-7) and insulin have some common downstream signaling effectors in HAEC (Sampaio et al 2007b) and in the hearts (Giani et al 2007). Ang-(1-7) induces the phosphorylation of the insulin downstream effectors PI3K and AKT via Mas in HAEC (Giani et al 2007, Sampaio et al 2007b) and IRS-1 and JAK2 via AT 1 receptor in hearts (Giani et al 2007). Moreover, Ang-(1-7)/Mas negatively regulates Ang II/AT 1 signaling in HAEC by promoting dephosphorylation of c-Src and ERK1/2 and inhibition of NADPH oxidase activity (Sampaio et al 2007a).…”
Section: Metabolic Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%
“…It has been reported that Ang-(1-7) and insulin have some common downstream signaling effectors in HAEC (Sampaio et al 2007b) and in the hearts (Giani et al 2007). Ang-(1-7) induces the phosphorylation of the insulin downstream effectors PI3K and AKT via Mas in HAEC (Giani et al 2007, Sampaio et al 2007b) and IRS-1 and JAK2 via AT 1 receptor in hearts (Giani et al 2007). Moreover, Ang-(1-7)/Mas negatively regulates Ang II/AT 1 signaling in HAEC by promoting dephosphorylation of c-Src and ERK1/2 and inhibition of NADPH oxidase activity (Sampaio et al 2007a).…”
Section: Metabolic Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%
“…Tissue samples were homogenized in solubilization buffer containing 1% Triton together with phosphatase and protease inhibitors, as described previously (17,33). Tissue extracts were centrifuged at 100,000 g for 1 h at 4°C to eliminate insoluble material, and protein concentration in the supernatants was measured using the Bradford method, as described previously (17,33). Equal amounts of solubilized protein (2 mg) were incubated at 4°C overnight with anti-IR or anti-IRS-1 antibodies at a final concentration of 4 g/ml.…”
Section: Tissue Homogenization Immunoprecipitation Western Blottingmentioning
confidence: 99%
“…Equal amounts of solubilized protein (2 mg) were incubated at 4°C overnight with anti-IR or anti-IRS-1 antibodies at a final concentration of 4 g/ml. Immune complexes were collected by incubation with protein A-Sepharose 6 MB, as described previously (17,33). SDS-PAGE and Western transfer of proteins to PVDF membranes were performed as described previously (17,33).…”
Section: Tissue Homogenization Immunoprecipitation Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in agreement with findings showing the cardioprotective effects of ANG-(1-7), a genetic deletion of the Mas receptor impaired heart function and changed the extracellular matrix to a profibrotic state [140]. After the activation of the Mas receptor, the intracellular signal transduction mechanisms that are involved in the following processes or tissues are poorly understood: i) in vivo, in the rat heart, ANG-(1-7) stimulated the phosphorylation of Janus kinase 2 (JAK2), insulin receptor substrate (IRS)-1 and Akt [141], ii) Mas receptor activation led to an increase in NO production via the phosphorylation of eNOS, a process that involves the activation of phosphatidylinositol 3-kinase-dependent Akt phosphorylation [142,143], and iii) upon the activation of the Mas receptor, MAPK phosphorylation is inhibited [144,145].…”
Section: Mas Receptormentioning
confidence: 99%